A novel multivariable prediction model for lymphatic dissemination in endometrioid endometrial cancer: The lymph node Metastasis Risk Index. (September 2019) - Meydanli, Mehmet M.; Aslan, Koray; Oz, Murat; Muftuoglu, Kamil H.; Yalcin, Ibrahim; Engin-Ustun, Yaprak
Abstract: Objective: The purpose of this study was to develop a risk assessment index that could determine which endometrioid endometrial cancer (EC) patients would benefit from a lymphadenectomy. Methods: The final pathology reports of 353 women who underwent complete surgical staging, including pelvic and para-aortic lymphadenectomy, for endometrioid EC between January 2008 and June 2018 were retrospectively reviewed. A logistic regression was used to investigate the clinicopathological factors associated with a positive nodal status. The independent risk factors for lymphatic dissemination were used to build a risk model and a "Lymph Node (LN) Metastasis Risk Index" was defined as follows: (tumor grade) × (primary tumor diameter) × (percentage of myometrial invasion) × (preoperative serum CA 125 level). The scores used in the LN Metastasis Risk Index were weighted according to the odds ratios assigned for each variable. The diagnostic performance of the model was expressed as the sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio. Results: The LN Metastasis Risk Index correctly identified 35 of 40 LN-positive women at a cutoff point of 981.0 (sensitivity: 87.5%, specificity: 86.3%, negative predictive value: 98.2%, positive predictive value: 44.9%, positive likelihood ratio: 6.37, and negative likelihood ratio: 0.14). The area under the receiver operating characteristic curve was 0.90 (95% confidence interval = 0.858–0.947) at this cutoff. The clinical accuracy of the model was 86.4%. When a cutoff point of <981.0 was selected in order to define those women at low-risk for lymphatic dissemination, our prediction model classified 275 women (77.9%) as being at low-risk for nodal involvement. Among these 275 women, 5 actually had positive LNs, which indicated a 1.8% false-negative rate. Conclusion: After external validation, the LN Metastasis Risk Index may be a valuable tool for the surgical management of endometrioid EC.